2021
DOI: 10.3390/v13061087
|View full text |Cite
|
Sign up to set email alerts
|

Replication Kinetics of B.1.351 and B.1.1.7 SARS-CoV-2 Variants of Concern Including Assessment of a B.1.1.7 Mutant Carrying a Defective ORF7a Gene

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of COVID-19, is a readily transmissible and potentially deadly pathogen which is currently re-defining human susceptibility to pandemic viruses in the modern world. The recent emergence of several genetically distinct descendants known as variants of concern (VOCs) is further challenging public health disease management, due to increased rates of virus transmission and potential constraints on vaccine effectiveness. We report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 19 publications
5
32
1
Order By: Relevance
“…We found substantial inhibition of SARS-CoV-2 VOC propagation, comparable to the original Munich patient isolate in Calu-3 cells using 100 μg/ml EPs 7630 ( Supplementary Figure S1A ). At low concentrations of 10 μg/ml EPs 7630, we did not detect a significant reduction of viral RNA levels, possibly as a consequence of increased replicative fitness reported for the analyzed VOCs ( Pyke et al, 2021 ; Rosenke et al, 2021 ; Touret et al, 2021 ). To exclude unspecific EPs 7630-induced inhibitory effects in Calu-3 cells, virus growth of other enveloped viruses, specifically mumps virus (MuV) and a Rift Valley fever virus (RVFV) clone 13-based reporter virus ( Kuri et al, 2010 ) was tested in the absence and presence of EPs 7630 ( Supplementary Figure S1B ).…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…We found substantial inhibition of SARS-CoV-2 VOC propagation, comparable to the original Munich patient isolate in Calu-3 cells using 100 μg/ml EPs 7630 ( Supplementary Figure S1A ). At low concentrations of 10 μg/ml EPs 7630, we did not detect a significant reduction of viral RNA levels, possibly as a consequence of increased replicative fitness reported for the analyzed VOCs ( Pyke et al, 2021 ; Rosenke et al, 2021 ; Touret et al, 2021 ). To exclude unspecific EPs 7630-induced inhibitory effects in Calu-3 cells, virus growth of other enveloped viruses, specifically mumps virus (MuV) and a Rift Valley fever virus (RVFV) clone 13-based reporter virus ( Kuri et al, 2010 ) was tested in the absence and presence of EPs 7630 ( Supplementary Figure S1B ).…”
Section: Resultscontrasting
confidence: 58%
“…In addition, EPs 7630 treatment efficiently reduced SARS-CoV-2 RNA levels in human lung cells infected with VOCs Alpha and Beta, highlighting its broadly-acting antiviral activity and the potential to inhibit newly emerging SARS-CoV-2 variants in the future. Although we detected reduced inhibition of VOC propagation at low concentrations, possibly due to the reported increase of replicative fitness for SARS-CoV-2 Alpha and Beta (Pyke et al, 2021;Rosenke et al, 2021;Touret et al, 2021), the broadly acting antiviral effects of EPs 7630 were clearly retained.…”
Section: Discussionmentioning
confidence: 57%
“…Our replication kinetics study using parental (lineage A), B.1, Alpha (B.1.1.7) and Beta (B.1.351) SARS-CoV-2 variants in CRFK cells stably expressing human ACE2 or hamster ACE2 revealed a comparatively higher replicative capacity of the Beta variant. This is consistent with the report of increased replication efficiency of Beta variant over Alpha variant in Vero cells [66]. In our experimental infection study using hamsters infected with parental virus (lineage A), Alpha (B.1.1.7) and Beta (B.1.351) VOC, more robust viral replication was observed in the nasal washes with the Beta VOC than the prototype virus or the Alpha VOC at 3 DPC, although the Beta variant inoculum titer was significantly lower than the inoculum dose of the other two viruses.…”
Section: Discussionsupporting
confidence: 93%
“…It is the subject of further exploration, whether the acquired mutations and in vitro/in vivo replication dynamics of Beta variant correlate with higher rate of transmissibility compared to other variants of concern. Pyke et al, have demonstrated quick replication of the Beta variant peaking at 48 hours post infection with considerably higher levels of virus replication compared to Alpha variant [ 25 ]. Apparently, the affinity of Beta RBD binding to ACE2 receptors is also found to be 2.7 fold higher than that of Alpha variant [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%